3-2-11. Peripheral nerve excitability changing in spinocerebellar ataxia type 6 (SCA6). Issue 6 (June 2017) - Osaki, Yusuke; Nodera, Hiroyuki; Izumi, Yuishin; Shimatani, Yoshimitsu; Chimeglkham, Banzrai; Oki, Ryosuke; Miyamoto, Ryosuke; Kawarai, Toshitaka; Kaji, Ryuji
Abstract: Motor nerve excitability testing in the median nerve with QtracS program (©Professor H. Bostock, UCL) was compared between 15 spinocerebellar ataxia type 6 (SCA6) patients and 22 age-matched healthy controls. Motor nerve excitability testing in tail nerve of 2 male mice was compared between before and after intraperitoneal injection of ω -agatoxin-IVA. Compared with normal controls, SCA6 showed statistically significant decrease of depolarizing threshold electrotonus ( p  < 0.006), increase of S2 accommodation ( p  < 0.003), and increase of late subexcitability in recovery cycle ( p  < 0.02), which were due to increased slow potassium currents. Both of two mice showed decrease of depolarizing threshold electrotonus and increase of threshold in recovery cycle after injection of ω -agatoxin-IVA. The present study indicates that motor nerves of SCA6 increase slow potassium currents derived from dysfunction of mutant protein, P/Q type voltage gated calcium channels.